Produção e acúmulo de substâncias com características de fitoalexina em folhas de fumo inoculadas do patógeno incompatível Pseudomonas syringue, pv. psi, com relação ao tempo - Duarte da Silva, Talmir; da Silva Romeiro, Reginaldo (Revista Ceres, 2025)
Tobacco leaves were innoculated with the incompatible pathogen Pseudomo- nas syringae pv. pisi by using the leaf infiltration technique. After 0, 6, 12, 24, 48, and 72 hours infil‘rated leaf tissue was harvested and extracted by the facilitated diffusion technique in 40% ethanol. The diffusates were concentrated in a flask evaporator and extracted with ethyl acetate. Quantification of antimicrobial activity in the extracts was then performed by using bioassays against Thiela- viopsis paradoza (bicautography and paper disc method) and Corynebacterium michiganense pv. michiganense (paper disc method). The concentration of antimi- crobial compounds was undetectable at zero time but showed a tendency to increase after some hours, remaining stable after 12-24 hours.